Management Mechanisms Aimed at Increasing the Efficiency of Resource Use in Industrial Enterprises - Avulchaeva Feruza Dzhurakuzievna (Academia Open, 2026)
General Background: Efficient resource utilization is a critical determinant of competitiveness and sustainability in industrial enterprises facing economic uncertainty and rising costs. Specific Background: In resource-intensive industries, particularly textile enterprises, traditional management approaches are insufficient to control material, labor, energy, and financial resources under dynamic market conditions. Knowledge Gap: Existing studies provide limited integrated frameworks that empirically link strategic, operational, and digital management mechanisms to measurable improvements in resource efficiency and financial performance. Aims: This study aims to analyze management mechanisms that enhance the efficiency of resource use in industrial enterprises through integrated strategic, operational, and digital tools. Results: The findings demonstrate that integrated management mechanisms improve material utilization, labor productivity, and energy efficiency, while reducing unit production costs, operational risks, and cost volatility, leading to stronger financial performance. Novelty: The study proposes a structured, block-based management mechanism that systematically connects resource planning, digital support, monitoring, and financial management. Implications: The results provide practical guidance for managers and policymakers to strengthen resource efficiency, cost optimization, and long-term competitiveness in industrial enterprises, particularly within the textile sector.Keywords : Resource Efficiency, Industrial Enterprise Management, Integrated Management Mechanisms, Digital Resource Management, Operational and Cost OptimizationHighlight : Integrated managerial systems significantly reduce material waste and stabilize input–output ratios across textile production stages. Digital tools enhance decision accuracy, real-time oversight, and operational consistency, strengthening productivity and risk control. Coordinated planning and monitoring improve cost structures, profitability, and financial resilience under volatile market conditions.